Effectiveness Of Use Of Nesting On Body Weight, Oxygen Saturation Stability, And Breath Frequency In Prematures In Nicu Room Gambiran Hospital Kediri City - Miftakhur Rohmah; Nurwinda Saputri; Justitia Bahari (STRADA : Jurnal Ilmiah Kesehatan, 2020)
This study used aapproach quasi- experimental with pre-post test group design in the NICU Room at Gambiran City Hospital in Kediri for the period 1 May 2019 to 31 July 2019. The population was 30 preterm infants. With purposive sampling technique, there were 14 samples of preterm infants. Group 1 consisted of 7 infants performed nesting for 5 days and group 2 consisted of 7 infants performed nesting for 7 days. Data normality test uses the Kolmogoro-Smirnov Test. Independent t test is used to test the effectiveness of using nesting on oxygen saturation, respiratory frequency stability and premature baby's weight. The results of the study in both groups p <α (0.05), then H0 is rejected and H1 accepted. So it can be concluded that the use of nesting in premature babies is effective in stabilizing body weight, oxygen saturation, the frequency of breathing of premature babies